Value of Contrast-Enhanced Ultrasound in Mummified Thyroid Nodules - Sijie Chen; Sijie Chen; Kui Tang; Kui Tang; Yi Gong; Fei Ye; Liyan Liao; Xiaodu Li; Xiaodu Li; Qi Zhang; Qi Zhang; Yan Xu; et al. (Frontiers in Endocrinology, 2022)
Mummified thyroid nodules (MTNs) are rarely reported and are usually misdiagnosed as malignant nodules. This article first reviewed the contrast-enhanced ultrasound (CEUS) enhancement features of 218 MTNs and classified them into three (A, B, C) patterns. The A pattern MTNs show linear hypo-enhancement, the B pattern MTNs show heterogeneous hypo-enhancement, and the C pattern MTNs show no enhancement in thyroid nodules. The A and C pattern enhancements of MTNs demonstrated a high specificity compared with the enhancement of previously reported typical papillary thyroid carcinomas (PTCs). To further study the B pattern MTNs, 24 B pattern MTNs and 42 PTCs were enrolled in this study, and CEUS parameters for each nodule were evaluated. Univariate analysis indicated that compared with PTCs, the B pattern MTNs more frequently exhibited heterogeneous hypo-enhancement and clear margins after clearance (p <0.05). A multivariate analysis revealed that heterogeneous hypo-enhancement and clear margins after clearance were independent characteristics related to the B pattern MTNs for differentiating them from PTCs (p <0.05). Thus, preoperative CEUS may provide more important information for distinguishing MTNs from malignant thyroid nodules to avoid surgical excisions or unnecessary fine-needle aspiration (FNA).